2017
DOI: 10.1186/s12891-017-1517-1
|View full text |Cite
|
Sign up to set email alerts
|

Anterior inferior plating versus superior plating for clavicle fracture: a meta-analysis

Abstract: BackgroundThe position of plate fixation for clavicle fracture remains controversial. Our objective was to perform a comprehensive review of the literature and quantify the surgical parameters and clinical indexes between the anterior inferior plating and superior plating for clavicle fracture.MethodsPubMed, EMBASE, and the Cochrane Library were searched for randomized and non-randomized studies that compared the anterior inferior plating with the superior plating for clavicle fracture. The relative risk or st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…There was no difference in peri-operative complication in either groups of their series. Placement of plate in either position carries the risk of iatrogenic neuro-vascular injury and neither position had significantly decreased risk [41] . In our study of 125 patients, all were treated by open reduction and superior placement of anatomical pre-contoured locking plate.…”
Section: Discussionmentioning
confidence: 96%
“…There was no difference in peri-operative complication in either groups of their series. Placement of plate in either position carries the risk of iatrogenic neuro-vascular injury and neither position had significantly decreased risk [41] . In our study of 125 patients, all were treated by open reduction and superior placement of anatomical pre-contoured locking plate.…”
Section: Discussionmentioning
confidence: 96%
“…Two recent meta-analyses investigated the effect of anteroinferior versus superior plating of the clavicle and they both concluded that plating along the superior and anteroinferior aspects of the clavicle leads to similar operative outcomes with respect to union, nonunion, malunion, and implant failure 25,26 . Only the meta-analysis by Nourian et al .…”
Section: Discussionmentioning
confidence: 99%
“… 62 , 66 It was found that anterior-inferior plating reduces the time to union, but the location of the plate does not seem to influence functional outcomes or infection rates. 63 …”
Section: Orif Using Plates and Screwsmentioning
confidence: 99%